2019
DOI: 10.1111/vco.12561
|View full text |Cite
|
Sign up to set email alerts
|

Definitive‐intent intensity‐modulated radiation therapy for treatment of canine prostatic carcinoma: A multi‐institutional retrospective study

Abstract: No standard of care is currently recognized for treatment of canine prostatic carcinoma (PC). This retrospective study assesses outcome following definitive‐intent, intensity‐modulated radiation therapy (RT) in dogs with PC. Medical records review was performed, including 18 patients from four institutions undergoing definitive‐intent intensity‐modulated radiotherapy to treat PC. Diagnosis was incidental in 7/18 (39%) patients. Five dogs (28%) had evidence of metastasis to loco‐regional lymph nodes at diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…13 More recently, another study reported on 18 dogs that had been treated using fullcourse RT (48-54 Gy). 14 Local progression was documented in 7 of 18 dogs at a median of 241 days after completing RT, and mOST was 563 days; EFS was longer with chemotherapy and shorter when metastases were identifiable at diagnosis; overall survival was longer in asymptomatic dogs. Results of these studies are promising for definitive intent RT for CGUC but the total number of reported cases remains low.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…13 More recently, another study reported on 18 dogs that had been treated using fullcourse RT (48-54 Gy). 14 Local progression was documented in 7 of 18 dogs at a median of 241 days after completing RT, and mOST was 563 days; EFS was longer with chemotherapy and shorter when metastases were identifiable at diagnosis; overall survival was longer in asymptomatic dogs. Results of these studies are promising for definitive intent RT for CGUC but the total number of reported cases remains low.…”
Section: Introductionmentioning
confidence: 93%
“…In a 2012 study describing clinical outcomes of 21 dogs having undergone full‐course intensity‐modulated and image‐guided radiotherapy (IM/IGRT; 54‐58 Gy in 20 daily fractions) with or without adjunctive drug treatment for CGUC, the subjective response rate was 60%, with a median event‐free survival (EFS) time of 317 days, and mOST of 654 days 13 . More recently, another study reported on 18 dogs that had been treated using full‐course RT (48‐54 Gy) 14 . Local progression was documented in 7 of 18 dogs at a median of 241 days after completing RT, and mOST was 563 days; EFS was longer with chemotherapy and shorter when metastases were identifiable at diagnosis; overall survival was longer in asymptomatic dogs.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, canine cancer is identified only after clinical signs have developed, by which point the disease is often advanced, the ability to provide long-term control is low, and the prognosis is poor. Just as for human cancer patients, early detection and treatment are considered essential for achieving the best possible clinical outcomes for canine cancer patients [ 2 , 3 ], and studies of cancers detected at earlier stages (including incidentally detected cases) in dogs have demonstrated improved outcomes [ 4 8 ]. In humans, organ-based cancer screening programs such as mammograms for women, prostate specific antigen (PSA) testing for men, and colonoscopies are well established and are covered by most insurance policies, as they have been proven to help detect cancers at earlier stages, when treatment is more effective, and a cure is more likely to be achieved [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical benefits of earlier cancer detection have been extensively documented in humans 55,60,89,100 as well as in dogs 15,17,22,58,70,72,73,77,92,102,103,111,112,114,119,123,125 , and major veterinary professional organizations have emphasized these benefits through statements such as "early detection is critical for the best outcome" and "neoplasia is frequently treatable and early diagnosis will aid [the] veterinarian in delivering the best care possible". 4,10 The introduction of novel cancer screening tools for dogs raises the important question of when to start screening for cancer.…”
Section: Discussionmentioning
confidence: 99%